Effectiveness and safety of furazolidone‐containing quadruple regimens in patients with Helicobacter pylori infection in real‐world practice. Issue 4 (20th May 2019) - Song, Conghua; Qian, Xing; Zhu, Yin; Shu, Xu; Song, Yanping; Xiong, Zhijuan; Ye, Jianfang; Yu, Tao; Ding, Ling; Wang, Hui; Lu, Nonghua; Xie, Yong
Abstract: Background & Aims: The eradication rate of Helicobacter pylori ( H pylori ) has decreased largely because of the antibiotic resistance. We aimed to evaluate the effectiveness and safety of furazolidone‐containing quadruple regimens for H pylori eradication. Methods: This was an observational study of furazolidone‐containing quadruple regimens for H pylori infection in real‐world settings. Data sets were collected from the medical records and telephone interviews of patients referred to a specialist clinic for suspected H pylori reinfection from January 1, 2015, to January 1, 2018, at the First Affiliated Hospital of Nanchang University. Main outcome measures were the eradication rate and adverse reactions during medication. Results: Among 584 patients with H pylori infection that met the inclusion criteria, 561 (96.1%) were treated for the first time, 19 (3.3%) had one, and 4 (0.5%) had two or more prior to furazolidone‐containing quadruple regimens. The eradication rates for 10‐day and 14‐day regimens were 93.7% (95% CI: 91.5%‐95.9%) vs 98.2% (95% CI: 95.6%‐99.3%), respectively ( P  = 0.098). Adverse drug reactions occurred in 8.2% (48/584) with abdominal discomfort being the most common symptom. Overall adverse events with 10‐day regimens were lower than 14‐day regimens (6.1% vs 17.4%, P  < 0.001). Logistic regression analysis indicated that poor adherence (adjusted odds ratio [AOR] = 46.5, 95% CI: 9.7‐222.4) was correlated with failed eradication. Adverse drug reactions during medication were related to smoking and tobacco status, alcohol intake history, regimens combined with tetracycline, and poor adherence (all P  < 0.05). Conclusions: Furazolidone‐containing quadruple regimens proved both safe and highly effective in a real‐world setting.